Self Care Management & Quality of Life of Coronary Heart Disease Patients during the Covid-19 Pandemic (STIKES Telogorejo Semarang, 2023)
Disease Heart Coronary (CHD) is disease degenerative that occurs Because existence narrowing and blockage vessels arteries that supply blood blood to in muscle heart . Height number relapse caused by Because existence a number of pattern maintenance less self Good so that influential to Quality His life . Purpose of research This For know connection between self care management with quality life CHD patients . Design study This use approach cross- sectional . The sampling technique used is purposive sampling with amount sample as many as 54 respondents sufferer Heart Coronary Clinic at Tugurejo Hospital Semarang Heart Clinic . Data collection using questionnaire self care management from Self-Care of Coronary Heart Disease Inventory (SC-CHDI) and World Health Organization Quality of Life-BREF ( WHOQOL-BREF) . Statistical test results use Spearman Rank isobtained results p value 0.000 (<0.05), with mark coefficient correlation 0.463. Based on results study obtained conclusion that there is connection between self care management with quality life CHD Patients During Covid-19 Pandemic at Tugurejo Regional Hospital Semarang. Recommendations from study This is for energy health can notice as well as increase self care management with give education management of PJK with well , so will influential to improvement quality life CHD patients . For study furthermore It is better to do services and programs related behavior For increase self care management and quality life CHD patients .